Association between childhood obesity and use of regular medications in the UK: longitudinal cohort study of children aged 5–11 years. Issue 6 (1st June 2015) - Solmi, Francesca; Morris, Stephen
Abstract : Objectives: Increasing rates of childhood obesity have been suggested as a possible cause for the increasing prevalence of chronic conditions among adults and children. Few studies have examined whether obese children are more likely to use medications than normal weight children. We investigate this association in the UK. Design: A panel study with repeated observations at ages 5, 7 and 11. Setting: A general population sample drawn from the Millennium Cohort Study, a UK-based birth cohort. Participants: A sample of 9667 children. Primary and secondary outcome measures: Our primary outcomes were crude and adjusted probabilities of taking any regular medications and the number of medications among overweight and obese children compared with normal weight children. Our secondary outcome was the distribution of medication use by therapeutic classification across body mass index (BMI) groups. Results: Obese children were more likely to use any medication (marginal effect (ME)=0.02, 95% CI 0.01 to 0.03) and to use more medications (ME=0.08, 95% CI 0.04 to 0.12) than normal weight children. Obese children used more medications for respiratory conditions than those of other BMI groups. Conclusions: Obese children are more likely to use regular medications and have comorbid conditions, even at young ages. This suggests that the cost of prescriptions should be considered when evaluating the economic burden of childhood obesity and that preventative strategies to reduce childhood obesity could be cost-effective in the short as well as in the long term. While more research is needed, both clinicians and policymakers should be aware of these findings when planning prevention and treatment strategies.